Chemokine (C-C motif) ligand 2 and coronary artery disease: Tissue expression of functional and atypical receptors. (February 2020) - Hernández-Aguilera, Anna; Fibla, Montserrat; Cabré, Noemí; Luciano-Mateo, Fedra; Camps, Jordi; Fernández-Arroyo, Salvador; Martín-Paredero, Vicente; Menendez, Javier A.; Sirvent, Juan J.; Joven, Jorge
Abstract: Chemokines, particularly chemokine (C-C- motif) ligand 2 (CCL2), control leukocyte migration into the wall of the artery and regulate the traffic of inflammatory cells. CCL2 is bound to functional receptors (CCR2), but also to atypical chemokine receptors (ACKRs), which do not induce cell migration but can modify chemokine gradients. Whether atherosclerosis alters CCL2 function by influencing the expression of these receptors remains unknown. In a necropsy study, we used immunohistochemistry to explore where and to what extent CCL2 and related receptors are present in diseased arteries that caused the death of men with coronary artery disease compared with unaffected arteries. CCL2 was marginally detected in normal arteries but was more frequently found in the intima . The expression of CCL2 and related receptors was significantly increased in diseased arteries with relative differences among the artery layers. The highest relative increases were those of CCL2 and ACKR1. CCL2 expression was associated with a significant predictive value of atherosclerosis. Findings suggest the need for further insight into receptor specificity or activity and the interplay among chemokines. CCL2-associated conventional and atypical receptors are overexpressed in atherosclerotic arteries, and these may suggest new potential therapeutic targets to locally modify the overall anti-inflammatory response.